Amperometric capsaicin biosensor based on covalent immobilization of horseradish peroxidase (HRP) on acrylic microspheres for chilli hotness determination - Mohammad R.; Ahmad M.; Heng L.Y. (Elsevier B.V., 2024)
Indexed WOS/SCOPUS/ERA